A Retrospective Comparative Outcomes and Cost Analysis of Office Based, Ultrasound Guided Renal Mass Biopsy Performed by Urologists and Standard Hospital Biopsies for Small Renal Masses. Issue 4 (July 2018) - Faraj, Kassem; Dave, Chirag N.; Patel, Kunal; Seifman, Brian; Vartanian, Stephen; Frontera, Rene; Nelson, Ryan; Hafron, Jason; Schervish, Edward W.
Abstract : Introduction : Renal mass biopsy is useful in the evaluation of small renal masses. We have previously reported that office based, ultrasound guided renal mass biopsy is safe, effective and feasible when performed by urologists. This study compares office based, ultrasound guided renal mass biopsy performed by urologists and hospital based renal mass biopsy. Methods : We retrospectively studied 70 patients who underwent office based, ultrasound guided renal mass biopsy and 155 who underwent hospital based, ultrasound or computerized tomography guided renal mass biopsy for evaluation of a small renal mass (4.0 cm or less) between January 2010 and February 2016. Results : A total of 70 patients underwent office based, ultrasound guided renal mass biopsy. Median age in this group was 69.5 years, median body mass index was 29.5 kg/m 2 and 61.4% of the patients (43) were male. A total of 103 patients underwent hospital based, ultrasound guided biopsy. Median age in this group was 68.0 years, median body mass index was 29.3 kg/m 2 and 53.4% of the patients (55) were male. Finally, 52 patients underwent hospital based, computerized tomography guided biopsy. Median age in this group was 69 years, median body mass index was 30.1 kg/m 2 and 51.9% of the patients (27) were male. Median tumor size was 2.7 cm in patients undergoing office based, ultrasound guided renal mass biopsy, 2.2 cm in those undergoing hospital based, ultrasound guided biopsy and 2.1 cm in those undergoing hospital based, computerized tomography guided biopsy (p = 0.001). Renal cell carcinoma was found in 43 of 70 (61.4%), 74 of 103 (71.8%) and 33 of 52 (63.5%) respective biopsies. Respective diagnostic rates were 81.4% (57 of 70 cases), 88.3% (91 of 103) and 86.5% (45 of 52, p = 0.434). Concordance with surgical pathology was 97.7% (42 of 43 cases), 100% (35 of 35) and 100% (15 of 15), respectively. Complication rates were 4.3% (3 of 70 patients), 13.6% (14 of 103) and 13.5% (7 of 52), respectively (p = 0.096). Cost analysis revealed that when available, office based, ultrasound guided renal mass biopsy provides the health care system a total savings of approximately $46, 011 yearly. Conclusions : Office based, ultrasound guided renal mass biopsy for small renal masses is a safe and efficacious option for select patients, and potentially offers greater convenience and availability as well as decreased health care costs.